Thru Reflect Line Calibration Kit For Radio Frequency Power Amplifier Characterisation - Hamid, Sofiyah Sal (2018)
Tremendous development in wireless mobile communication and microwave measurement increase the demand for accuracy and performance characterizations of wireless device over various frequency. Due to this fact, advance calibration technique with better features are developed to remove measurement errors. This thesis focuses on development of Through-Reflect-Line (TRL) calibration standard kit that meets the requirement for power amplifier characterization operating in the range of frequency from 2.5 GHz to 2.57 GHz in order to meet stringent linearity requirement. The design of the TRL calibration kit were performed using Advanced Design System (ADS). The first double layer design was fabricated on Duroid RO4003C with a dielectric permittivity of 3.38 and thickness of 0.813 mm. Meanwhile, the second multilayer design was fabricated on Hitachi MCL E-679 laminated microwave board with dielectric permittivity of 4.4 and the thickness of 1.2 mm. Verification of the proposed design and technique were accomplished through hardware measurement. This technique has been compared with the conventional Short-Open-Load-Through (SOLT) calibration technique in terms of the gain, S21. As for the conventional technique, the PA gain for double layer designs are 24.598 dB and 24.15 dB, while for multilayer design are 26.5 dB and 25.981 dB. Both were measured at 2.505 GHz and 2.565 GHz, respectively. On the other hand, with the proposed TRL calibration kit, the gain of the Power Amplifier for double layer design are 24.823 dB and 24.406 dB while for multilayer design are 27.92dB and 27.408dB at 2.505 GHz and 2.565 GHz. As a result, an improvement of approximately 10% from the conventional calibration technique was achieved. The measurement result indicates that the TRL calibration is more accurate than the SOLT calibration method which significantly improve the performance of the PA. Besides, the implementation of this technique has been proved be efficient as the gain is enhanced by reducing the systematic errors.